1992
DOI: 10.1002/j.2333-8504.1992.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of Computer and Paper‐and‐pencil Scores for Two Clep® General Examinations

Abstract: This report describes two studies that investigated the comparability of scores from paper‐and‐pencil and computer‐administered versions of the College‐Level Examination Program (CLEP) General Examinations in Mathematics and English Composition. The first study used a prototype computer‐administered version of each examination. Based on the results of the first study and feedback from the study participants, several modifications were made to these prototype versions. A second study was then conducted using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 4 publications
0
30
1
1
Order By: Relevance
“…In a later study, Mazzeo et al (1991) reaffirmed the need to determine empirically the equivalence of computer and paper versions of an examination. Additionally, Kolen and Brennan (1995) argue that mode effects of paper-and-pencil and computer-based tests are complex and that the extent to which effects are present are likely dependent on the particular testing programme.…”
Section: Item Layout and Presentation Of Graphicsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a later study, Mazzeo et al (1991) reaffirmed the need to determine empirically the equivalence of computer and paper versions of an examination. Additionally, Kolen and Brennan (1995) argue that mode effects of paper-and-pencil and computer-based tests are complex and that the extent to which effects are present are likely dependent on the particular testing programme.…”
Section: Item Layout and Presentation Of Graphicsmentioning
confidence: 94%
“…This complexity also suggests that separate analyses for modal sensitivity are necessary for any test offered in both formats. Finally, Mazzeo et al (1991) recommended examining relative effects of mode of administration among subpopulation groups, which, over a decade later, is still not a factor commonly studied.…”
Section: Item Layout and Presentation Of Graphicsmentioning
confidence: 99%
“…They measured students' perceptions toward the use of an online exam as an assessment tool on university campus within a Decision Support System Course at Al al Bayt University [7]. Mazzeo, Druesne, Raffeld, Checketts, & Muhlstein (1991) showed that paper-based test scores were greater than computer-based test scores for both mathematics and English CLEP tests [8]; although studies of Schaeffer, Reese, Steffen, McKinley, & Mills (1993) have reported no difference between computer and paper-based tests [9]. This paper presents the results of comparative study between paper based and online exams conducted on a group of Tabuk university students, who had no prior experience of taking online exams, in the region of Tabuk, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Although Lee had intended to create an interval-level scale based on these questions, she reported that "due to skewness, restricted variance, and low Cronbach's alpha, it was decided to use the CEQ scores to form a categorical variable" (p. 729). The CEQ was subsequently modified and used in two studies by Mazzeo, Druesne, Raffeld, Checketts, and Muhlstein (1991). Unlike Lee's scale, Mazzeo et al summed the values ofthe responses, creating an interval-level scale with values ranging from 6 to 27; this scale was not analyzed for its psychometric properties.…”
Section: Introductionmentioning
confidence: 99%